Development of Electronic Student Worksheets Based on the Discovery Learning Model to Facilitate Mathematical Understanding Ability of Class XI SMA/MA Students in Limit Function Material - Nur Aisyah; Kartini; Titi Solfitri (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2022)
This research is motivated by the importance of students' mathematical understanding abilities in Indonesia, especially in Riau Province and the limited number of Student Worksheets that facilitate mathematical understanding abilities. Mathematical understanding is important for students because it becomes a prerequisite for further mathematical concepts, and meaningful learning will last longer. In facilitating students' mathematical understanding skills, meaningful learning is needed. One such learning is the Discovery Learning (DL) model. Applying a learning model alone is not enough to support the realization of an active learning process that can develop students' mathematical understanding abilities. Therefore, a teacher must provide facilities to support students, including developing Student Worksheets. Using appropriate digital technology in learning facilitates and attracts students' interest in learning so that learning becomes more effective. One of the sites that can make student worksheets more interactive by adding media in the form of motion animation, audio and video to it is a live worksheet. This study aimed to produce a product in the form of an electronic student worksheet based on the Discovery Learning (DL) model to facilitate mathematical understanding skills in class XI SMA/MA students on valid and practical Limit Function material. This research uses the ADDIE development model (Analysis, Define, Design, Development, and Evaluation). The resulting product is stated to be very valid and practical with an average percentage validity of 90%, and the average value of the questionnaire response results for students by 83%.